Cajal and the Spanish Neurological School: Neuroscience Would Have Been a Different Story Without Them - de Castro, Fernando (Frontiers in Cellular Neuroscience, 2019)
Santiago Ramón y Cajal was still young when he came across the reazione nera, discovered by the Italian Camillo Golgi. Cajal became absolutely entranced by the fine structure of the nervous system this technique revealed, which led him to embark on one of the last truly epic endeavors in modern History: the characterization of nervous cells, and of their organization to form the brain. Cajal remained in Spain throughout his scientific career, working for years alone. With international recognition, Cajal began recruiting brilliant students as collaborators. A handful of his pupils also made decisive discoveries that served to lay the foundations of modern Neuroscience. Cajal´s brother Pedro, Tello, Domingo Sánchez, Achúcarro, Lafora, Río-Hortega, de Castro and Lorente de Nó worked side by side with El Maestro. While Cajal himself pronounced some of the basic rules that have helped us to understand the nervous system (the neuron theory, the law of dynamic polarization of the neuron), as well as providing innumerable details about the histological organization of the different neural structures, it was Pío del Río-Hortega who identified two of the four main cell types in the CNS (oligodendrocytes and microglia), and Fernando de Castro who described the innervation of the blood vessels and identified the first chemoreceptors in the carotid body. Together, this group of scientists is known as the Spanish Neurological School, and if they had not existed the History of Neuroscience would surely have been quite a different story; and proof that Cajal was a truly exceptional scientist but he was not an exception for Spanish Science.